The Influence Of Temperature And Longing Of Soak Towards Absorbing Water In The Basic Of Denture Thermoplastic Nylon - Fadhilah, Alfi; Dwi Atmaja, Widyapramana (Insisiva Dental Journal, 2013)
Thermoplastic nylon is a polymer synthetic used as the basic material of denture and able to absorb water because of the existence of polar element (COOH-), so that it is hydrophilic. Water is absorbed through diffusionÂ process which the diffusion coefficient is influenced by temperature and time of longing of soak will raise theÂ absorbing water till saturation point. The goal of this research is for knowing the influence of temperature andÂ longing of soak towards absorbing water in the basic of denture thermoplastic nylon. The research uses samplethermoplastic nylon with size of diameter x height (50Â±1mm x 0.5Â±0.1mm) as much as 15 samplesÂ which is divided into 3 groups, previous mass each of sample and also measured the volume. Empty the sampleÂ into beaker glass fulfilled of aquades 100ml then incubated. The first group is incubated in 250C, the secondÂ group 370C, the third group 550C, observed in 5 days, every 24 hours the samples are balanced their changing ofÂ mass. The results are formulated with (m1 â m0)/V, then analyzed with Two Way Anova and LSD0,05. Theresult of testing Two Way Anova that is the temperature able to influence (p=0,000<0,05), longing ofÂ soak able to influence (p=0,000<0,05), while the temperature and longing of soak are not influenced towardÂ the absorbing water in the basic of denture thermoplastic nylon, because p=0,994>0,05.